Genome-Wide Association Studies of Salt Tolerance at Seed Germination and Seedling Stages in Brassica napus - Zhang, Guofang; Zhou, Jinzhi; Peng, Yan; Tan, Zengdong; Li, Long; Yu, Liangqian; Jin, Cheng; Fang, Shuai; Lu, Shaoping; Guo, Liang; Yao, Xuan (Frontiers in Plant Science, 2022)
Most crops are sensitive to salt stress, but their degree of susceptibility varies among species and cultivars. In order to understand the salt stress adaptability of Brassica napus to salt stress, we collected the phenotypic data of 505 B. napus accessions at the germination stage under 150 or 215 mM sodium chloride (NaCl) and at the seedling stage under 215 mM NaCl. Genome-wide association studies (GWAS) of 16 salt tolerance coefficients (STCs) were applied to investigate the genetic basis of salt stress tolerance of B. napus. In this study, we mapped 31 salts stress-related QTLs and identified 177 and 228 candidate genes related to salt stress tolerance were detected at germination and seedling stages, respectively. Overexpression of two candidate genes, BnCKX5 and BnERF3 overexpression, were found to increase the sensitivity to salt and mannitol stresses at the germination stage. This study demonstrated that it is a feasible method to dissect the genetic basis of salt stress tolerance at germination and seedling stages in B. napus by GWAS, which provides valuable loci for improving the salt stress tolerance of B. napus. Moreover, these candidate genes are rich genetic resources for the following exploration of molecular mechanisms in adaptation to salt stress in B. napus.